Pengaruh Profitabilitas, Gender Diversity Dewan Komisaris dan Dewan Direksi Terhadap Kebijakan Dividen - Fitria, Citra Nanda; Sholichah, Mu'minatus (Journal of Culture Accounting and Auditing, 2023)
This study aims to determine the influence of profitability, gender diversity of the board of commissioners and advisory boards on dividend policy. The sample population was taken from all manufacturing companies listed on the Indonesia Stock Exchange for 2020 - 2021. The sampling technique was purposive sampling which obtained 54 companies. There were 108 samples tested. Data were collected using secondary data from all manufacturing companies listed on the Indonesia Stock Exchange. Testing this hypothesis uses multiple linear regression tests with SPSS version 22 software. The results of this study indicate that the effect of profitability and gender diversity of the board of commissioners has an effect on dividend policy. While the advisory board has no influence on dividend policy.